2014
DOI: 10.14202/vetworld.2014.21-25
|View full text |Cite
|
Sign up to set email alerts
|

Association between the seminal vesicle weight and certain steroids in buffaloes (Bubalus bubalis)

Abstract: Aim: Present study was carried out to study the association of seminal vesicle weight with steroidal (testosterone and estrogen) concentration in buffalo bulls. Materials and Methods:A total of 30 pairs of seminal vesicles were collected from buffalo bulls (irrespective of age and breed) and categorized into group I (<5 gm), group II (5-8 gm) and group III (>8 gm) on the basis of mean seminal vesicles weight for establishing relationship. Results:The mean concentration of testosterone in seminal vesicle fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
2
2
1
Order By: Relevance
“…Testosterone also showed a significant positive correlation with SC and SVs weight, and thus, estimation of circulating testosterone can be used as a measurable marker of organ (SC and SVs) weight, function, and libido. In male buffaloes, Shinde [ 15 ] reported a significant correlation between SV fluid testosterone and SV weight contrary to the present findings. The present studies also demonstrated ascending increase in testosterone concentration as per SV weight and dentition age.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Testosterone also showed a significant positive correlation with SC and SVs weight, and thus, estimation of circulating testosterone can be used as a measurable marker of organ (SC and SVs) weight, function, and libido. In male buffaloes, Shinde [ 15 ] reported a significant correlation between SV fluid testosterone and SV weight contrary to the present findings. The present studies also demonstrated ascending increase in testosterone concentration as per SV weight and dentition age.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, size/weight and function of SVs could be predicted by measuring SC and testosterone as SVs registered a significant correlation with SC and plasma testosterone. Contrary to the present observation, a significant positive correlation was reported between SV weight and SV fluid testosterone in male buffalo [ 15 ]. The present study also recorded a significant effect of dentition age on SVs weight comparable to findings in water buffalo [ 26 ], while in another report, SV weight was lower in immature and mature buffalo bulls [ 17 ] possibly due to less number of observations and due to varying age and nutritional status which govern growth.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Telah diketahui bahwa sapi jantan memiliki organ vesikula seminalis yang mampu mensekresikan berbagai jenis hormon seperti testosteron, estrogen, dan prostaglandin (Pemayun dkk, 2012;Shinde et al, 2014). Kelenjar vesikula seminalis pada sapi berbentuk kompak berlobus dan memiliki duktus sekretori/saluran pengeluaran intralobularis yang berbentuk sedikit melingkar dan bergabung menjadi duktus sekretori utama.…”
Section: Pendahuluanunclassified
“…The variation in concentration and number of HBPs within and between the bulls might be due to testosterone dependent secretary activity of accessory sex glands [9], health status of accessory sex glands [26] and inherent character of an individual bull. Furthermore, aggregation product of low molecular weight proteins or degradation product of high molecular weight proteins [13] may alter the HBPs profile of a bull.…”
Section: Hbps Concentration and Electrophoretic Profilementioning
confidence: 99%